Nutritional evaluation of dual purpose barley as fodder - HUNDAL, J S; KUMAR, BALWINDER; WADHWA, M; BAKSHI, M P S; RAM, HARI (The Indian Journal of Animal Sciences, 2014)
The present study was taken up to assess the effect of N scheduling on the fodder and grain yield and on the nutritional worth of green fodder obtained from grain (RD–2552) and dual purpose (RD-2035) barley (Hordeum vulgare L.) varieties. The crop of both the cultivars was harvested 55 days after sowing (DAS) and was used as fodder. Nitrogen fertilizer (urea) was applied @ 87q/ha, either 50% at the time of sowing and 50% after 55 DAS (T1); 50% at the time of sowing, 25% after 55 DAS and 25% after next irrigation i.e. 80 DAS (T2); 33% at the time of sowing, 33% after 55 DAS and 33% after 80 DAS (T3); 33% at the time of sowing and 67% after 55 DAS (T4) or 67% at the time of sowing and 33% after 55 DAS (T5). Both the varieties of barley were cultivated in 1.15 m × 7.0 m plots in triplicate at the Ludhiana campus of Punjab Agricultural University for 2 consecutive years. The data were analyzed statistically by using 2 × 5 factorial design. The dual purpose variety, irrespective of N-scheduling, gave significantly higher fodder and significantly lower grain yield as compared to grain variety. The N-scheduling, irrespective of the genotype, did not have any significant effect on the fodder yield in 2008–09, but during 2009– 10 significantly higher fodder yield was observed in T5 as compared to T3 and T4 N- scheduling. While reverse trend was observed in grain yield i.e. it was highest in T4 followed by T3, but lowest in T1 N-scheduling in both the years of cultivation. The grain variety had significantly higher total ash, CP and hemicellulose content, while the dual purpose variety had significantly higher ADF and cellulose content. The T2 N-scheduling resulted in the highest CP and EE content and lowest cell wall constituents. The net gas production, digestibility of nutrients, VFA production and ME availability were significantly higher in the fodder of grain variety as compared to dual purpose barley variety. The N-scheduling showed no significant effect on above parameters. It was concluded that grain variety (RD-2552) had high grain and straw yield but low green fodder yield with better nutritional quality as compared to dual purpose barley variety (RD-2035).